On Bipolar Complex Fuzzy Hv-subgroups - Sanem Yavuz; SERKAN ONAR; Bayram Ali Ersoy (Journal of Hyperstructures)
The target of this article is to peruse bipolar complex fuzzy subhypergroups (Hv−subgroups) by employing bipolarcom-plex fuzzy sets and hyperstructures besides of this some related properties are debated.Furthermore, the notion of bipolar complex anti-fuzzy subhyper-groups (Hv−subgroups) is presented. Their characteristics and their connections with bipolar complex fuzzy and anti-fuzzy sub-hypergroups (Hv−subgroups) are proposed, with several examples demonstrating these concepts.